Notas do Coletivo Hildete Bahia acerca do racismo estrutural e da educação / Notes from the Hildete Bahia Collective on structural racism and education - Mota, Marina Soares; de Oliveira, Michele Mandagará; Rodrigues, Wendel Farias (Journal of Nursing and Health, 2020)
-